An Assessment of Physicians’ Recommendations for Colorectal Cancer Screening and International Guidelines Awareness and Adherence: Results From a Thai National Survey - Pausawasdi, Nonthalee; Tongpong, Pongkamon; Geeratragool, Tanawat; Charatcharoenwitthaya, Phunchai (Frontiers in Medicine, 2022)
Abstract Background: Colorectal cancer (CRC) screening uptake is generally low in the Asia Pacific and physicians’ recommendations affect the screening participation. Objective: The study aimed to assess Thai physicians’ recommendations for CRC screening, the awareness of the international guidelines, and adherence. Methods: A survey containing questions assessing physicians' demographic data, screening recommendations, and awareness of the international CRC screening guidelines assessed by clinical vignettes. Independent predictors of physicians’ recommendations for CRC screening were determined by logistic regression analysis. Results: 586 of 1,286 (46%) physicians completed the survey, and 58% of them offered CRC screening. The majority of colorectal surgeons (91%) and gastroenterologists (86%) endorsed screening, whereas 35% of primary care physicians recommended screening. The patient's age was the only factor influencing physician's decision to offer screening (OR, 2.75: 95%CI, 1.61-4.67). Colonoscopy was the most recommended modality among specialists, whereas 60% of primary care physicians offered fecal occult blood tests. The guidelines awareness was noted in 81% of participants, with the highest rates among gastroenterologists and colorectal surgeons. Gastroenterologists were more likely to adhere to the guidelines than surgeons, but both recommended shorter interval surveillance colonoscopy than guidelines recommendations in cases of small hyperplastic rectosigmoid polyps. Conclusions: Recommendations for CRC screening and awareness of guidelines vary among different specialties. The necessity of CRC screening should be emphasized among PCPs. The factors influencing colorectal surgeons' and gastroenterologists' lack of adherence to guidelines in hyperplastic polyp surveillance should be explored.